Penggunaan Gaya Bahasa Dalam Lirik Lagu - Muhammad Rakha Purnama; Sayyed Mohammad Fadillah (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This research aims to analyze the use of figurative language in song lyrics. The research method employed is qualitative with a descriptive approach. Data were collected through a literature review of relevant books and journal articles. Content analysis technique was used to identify, classify, and describe the use of figurative language such as metaphor, simile, personification, hyperbole, repetition, antithesis, rhetorical question, litotes, and sarcasm in song lyrics. The findings indicate that these figurative language devices are used to enrich the text with emotional and aesthetic nuances. Metaphors and similes provide vivid and detailed imagery, while personification animates non-human objects. Hyperbole and repetition create dramatic effects and emphasis, whereas antithesis highlights contrasts and conflicts within the song's theme. Rhetorical questions engage listeners in reflection, while litotes convey meaning subtly yet effectively. Sarcasm is employed for sharp criticism and satire expressing dissatisfaction or disagreement. In conclusion, figurative language is a crucial element in song lyrics that enhances not only the text but also the appeal, expression, and meaning in the experience of listening to songs.